2017
DOI: 10.1097/mib.0000000000001054
|View full text |Cite
|
Sign up to set email alerts
|

A Fixed Stricture on Routine Cross-sectional Imaging Predicts Disease-Related Complications and Adverse Outcomes in Patients with Crohnʼs Disease

Abstract: Information from radiologic studies, especially the presence of fixed strictures, can predict future CD complications. These findings, along with smoking and ongoing inflammation, should alert the clinician to the possibility of future complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…In our study, we found that stenosis was 25 cases, of which 24 cases were active, mesenteric hypervascularity (comb sign) was 32 cases, of which 28 cases were active, and 8 cases showed mesenteric enlarged lymph nodes, which were active. Several studies have reported that stenosis was related to the activity of the lesion [ 4 , 12 ]. Chaudhry et al [ 12 ] found that stenosis and the other complications, such as fistula and abscess, were reciprocal causation and affected the prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that stenosis was 25 cases, of which 24 cases were active, mesenteric hypervascularity (comb sign) was 32 cases, of which 28 cases were active, and 8 cases showed mesenteric enlarged lymph nodes, which were active. Several studies have reported that stenosis was related to the activity of the lesion [ 4 , 12 ]. Chaudhry et al [ 12 ] found that stenosis and the other complications, such as fistula and abscess, were reciprocal causation and affected the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that stenosis was related to the activity of the lesion [ 4 , 12 ]. Chaudhry et al [ 12 ] found that stenosis and the other complications, such as fistula and abscess, were reciprocal causation and affected the prognosis. Sakurai et al [ 13 ] reported that comb sign and mesenteric enlarged lymph nodes were important predictors of mucosal ulceration; It is worth noting that the size of the ulcer and affected area is the most important part of the CD endoscopy score.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a proximal (upstream) stenosis with obstructive properties and a distal collapsed bowel (downstream), further aboral stenosis (tandem stenoses) can be masked. The diagnostic requirement of a prestenotic dilation may thus reduce the sensitivity for the detection of stenosis [44][45][46][47][48]. Stenoses suspected on MRE without verified prestenotic dilation should therefore be described as "probable stenosis".…”
Section: Recommendationmentioning
confidence: 99%
“…Die aktuell gängige Definition beschreibt eine Einengung des Lumens mit einer prästenotischen Dilatation > 25 mm des vorgeschalteten Darmsegments [16,54,55]. Die Forderung nach einer prästenotischen Dilatation reduziert möglicherweise die Sensitivität für die Detektion von Stenosen [56,57,58,59,60]. Der Vorteil der Darmsonografie liegt darin, dass die Motilität des vorgeschalteten Darmsegmentes zur Identifizierung der Stenose als Kriterium mit herangezogen werden kann.…”
Section: Stenosierender Morbus Crohnunclassified